Analisis Arketipe Tokoh Nawawi Dalam Novel Introver Sebuah Novel Penggugat Jiwa Karya M. F Hazim - Candra Galih Wicaksono; Naufal Nur Nafis; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is to find out the archetypes of Nawawi characters using literary psychology studies. The Introvert Novel, a soul-stirring novel by M.F Hazim, is interesting to discuss and explore with Carl Gustav Jung's theory, knowing the personality of the main character named Nawawi. The method used is descriptive qualitative and uses Carl Gustav Jung's psychoanalytic theory to discover the personality of the Nawawi character. In summary, it can be explained that descriptive qualitative is a research method that operates on a simple qualitative approach with an inductive flow. This inductive flow means that qualitative descriptive research begins with an explanatory process or event from which finally a generalization can be drawn which is a conclusion from the process or event. The findings from this research are that the Nawawi character has a persona archetype that is used to cover his true personality, the shadow that appears jealousy of why his friends can chat and socialize and he doesn't adapt, and relatedly, the anima that arises in his mind of liking women according to his ideal woman.